2019
DOI: 10.1080/02670836.2019.1618620
|View full text |Cite
|
Sign up to set email alerts
|

A medium-Mn steel processed by novel twin-roll strip casting route

Abstract: A medium-Mn steel (Fe–0.3C–4Mn–1.82Al–0.6Si wt-%) was produced by a novel processing route involving twin-roll strip casting, hot rolling and intercritical annealing (IA). Macrosegregation was absent in the as-cast strip. The microstructure of the as-cast strip consisted of martensite and austenite (∼10 vol.-%), and the solidification structure was characterised by dendritic structure. With an increase in IA temperature from 680 to 725 and to 755°C, austenite fraction in intercritically annealed steels was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…13-U30 diagram comparing alloying cost and energy absorption between several medium Mn steels in the literature and commerical steels. [2,3,5,7,12,13,35,39,40,[63][64][65][66][67][68][69] *ThyssenKrupp dual phase steels.…”
Section: Effect Of Cold Rolling On Yield Point Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…13-U30 diagram comparing alloying cost and energy absorption between several medium Mn steels in the literature and commerical steels. [2,3,5,7,12,13,35,39,40,[63][64][65][66][67][68][69] *ThyssenKrupp dual phase steels.…”
Section: Effect Of Cold Rolling On Yield Point Elongationmentioning
confidence: 99%
“…For example, recent advances in strip casting technology have shown that medium Mn steel can be successfully cast into 2.5 mm thick strip. [12] With this in mind, reliance on cold rolling for heavy gauge reduction can be reduced. Cold rolling can then be pushed to the end of the processing route (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the composition window where the TWIPþTRIP mechanism is active is usually very narrow. [10] Nevertheless, Wang et al [11] showed that microsegregation in a fairly lean medium Mn steel could be avoided by twin roll casting. Their steel of composition Fe-4Mn-1.8Al-0.6Si-0.3C with a cast thickness of 2.5 mm did not show significant microsegregation and was also able to demonstrate the TWIP þ TRIP effect after final processing.…”
Section: Introductionmentioning
confidence: 99%
“…al. [11] showed that microsegregation in a fairly lean medium Mn steel could be avoided by twin roll casting. Their steel of composition Fe-4Mn-1.8Al-0.6Si-0.3C with a cast thickness of 2.5 mm did not show significant microsegregation and was also able to demonstrate the TWIP+TRIP effect after final processing.…”
Section: Introductionmentioning
confidence: 99%